Acquisition of Noun Inflection in Lithuanian as a Foreign Language: a Qualitative Study - Dubasava, Anzhalika (Respectus Philologicus, 2020)
The aim of the research was to investigate how native speakers of Russian, which is a highly complex inflectional language, cope with the acquisition of the similar by structure and complexity Lithuanian language. The subjects were adults of different age and education who learned Lithuanian in Belarus. I analyse errors related to the acquisition of noun case. The errors are divided into formal (acquisition of endings) and conceptual ones (choice of the appropriate case). I shortly compare my results with the results of similar research conducted in Lithuania where the subjects were native speakers of different languages.The results of the study show that similar errors are typical for native speakers of different languages irrespective of their morphological complexity. A complex inflectional system of a native language is not necessarily beneficial, but it seems to give some advantages for the acquisition of semantic (not syntactic) cases.